Correlation between serum-ascites albumin gradient (SAAG) and esophageal varices in patients with portal hypertension - Zaezafon, Hasan; Dogman, Dad; Swede, Killed (Latakia University Journal -Medical Sciences Series, 2018)
Introduction: Esophageal varices (EV) and ascites are two major findings of portal hypertension (PTHN). Several studies have evaluated possible noninvasive markers of EVs in patients with portal hypertension. Aim: This study was conducted to determine the correlation between the serum-ascites albumin concentration gradient (SAAG) and the incidence of esophageal varices (EV) and its grades in patients with ascites due to (PHTN). Materials and Methods: Our study was conducted at Alassad and Tishreen University Hospitals during the period between March 2016 – March 2017. The study included 76 patients with ascites, demonstrated by ultrasonography, who had measurement of the SAAG. All had upper gastrointestinal endoscopy to assess of the presence and size of EV. High SAAG was considered to be present when SAAG was ≥ 1.1 g/dl and Low SAAG when it was < 1.1 g/dl. Results: We found that 60 of 76 (79%) patients had High SAAG and 16 of 76 (21%) had Low SAAG. Esophageal varices were present in 40 of 60 (66.7%) patients with High SAAG and in none of 16 (0%) patients with Low SAAG (p<0.05) that means, there is a direct relation between high SAAG and the presence of EVs. We found a direct relation between the level of SAAG and the presence of EVs (P<0.05) in patients with high SAAG ascites. The size of the EV did not demonstrate significant statistical association with the degree of SAAG in patients with High SAAG (P=0.32). Using the Receiver- Operating-Characteristic Curve a SAAG value of ≥ 1.5 g/dl was an accurate indicator of the presence of EV (cutoff point for the higher predictive value : positive 82.5% and negative 65 % ، accuracy : 76.7%). We also found no difference in the presence of EV between alcoholic and non-alcoholic cirrhosis (P = 0.4). There is a direct relation between the severity of liver disease according to Child-Pugh classification and the presence of EVs (P=0.00008) in patients with liver cirrhosis. Conclusion: The serum-ascites albumin concentration gradient (SAAG) can predict the presence of Esophageal varices (EVs) in patients with portal hypertension (PHTN), but does not allow to predict the degree of varices. Keywords: Ascites, Portal Hypertension (PHTN), Esophageal varices (EV), Serum-ascites albumin concentration gradient (SAAG). العلاقة بين مدروج ألبومين المصل- الحبن(SAAG) ودوالي المري لدى مرضى ارتفاع توتر وريد الباب مقدمة: يعتبر كل من دوالي المري والحبن موجودتان كبيرتان لارتفاع توتر وريد الباب. أُجريت دراسات عديدة لتقييم المُشعرات التنبؤية غير الغازية التي تقترح حدوث دوالي المري عند مرضى ارتفاع توتر وريد الباب. الهدف: هدف الدراسة هو تحديد العلاقة بين مدروج ألبومين المصل والحبن (SAAG) وحدوث دوالي المري ودرجتها إن وجدت عند مرضى الحبن التالي لارتفاع توتر وريد الباب. المواد و الطرق: تمت الدراسة في مستشفيي الأسد و تشرين الجامعيين في الفترة الممتدة بين آذار 2016 و آذار 2017 .شملت الدراسة 76 مريضاً لديهم حبن مشخص بالتصوير بالإيكو ، تم قياس المدروج (SAAG) لهؤلاء المرضى ، خضع جميع المرضى لتنظير هضمي علوي لتقييم وجود ودرجة دوالي المري. تم اعتبار قيم المدروج مرتفعة عندما يكون SAAG ≥ 1.1 غ/دل. ومنخفضةً عندما يكون SAAG > 1.1 غ/دل. النتائج: وجدنا أن 60 مريضاً من أصل 76 (79%) لديهم حبن مرتفع المدروج , و 16 مريضاً من أصل 76 (21%) لديه حبن منخفض المدروج. وجدت دوالي المري عند 40 مريضاً (66.7%) من أصل 60 مريضاً لديهم حبن مرتفع المدروج ، و لم تشاهد دوالي المري عند أي من مرضى الحبن منخفض المدروج (0%) ( P<0.05) ، أي هناك علاقة مباشرة بين الحبن مرتفع المدروج وحدوث دوالي المري. كذلك وجدنا أن هناك علاقة مباشرة بين قيمة المدروج SAAG وحدوث دوالي المري (P<0.05) عند مرضى الحبن مرتفع المدروج. لم نلاحظ وجود ترافق إحصائي هام بين قيمة SAAG و درجة دوالي المري عند مرضى الحبن مرتفع المدروج (P=0.32). باستخدام منحنى ROC: فإن قيمة SAAG ≥ 1.5 غ/دل تترافق مع حدوث دوالي مري بقيمة تنبؤية إيجابية: 82.5% وقيمة تنبؤية سلبية : 65% ودقة تشخيص : 76.7% لم يكن هناك فرق في حدوث دوالي المري لدى المرضى الذين لديهم حبن مرتفع المدروج بسبب التشمع الكحولي أو التشمع غير الكحولي (P=0.4) ، كما وجدنا أن هناك علاقة مباشرة بين شدة المرض الكبدي مقدرةً وفق تصنيف Child-Pugh وبين حدوث دوالي المري (P=0.0008 ) عند مرضى ارتفاع توتر وريد الباب بسبب تشمع كبد. الخلاصة: إن مدروج ألبومين المصل -الحبن (SAAG) يسمح بالتنبؤ بحدوث دوالي المري عند مرضى ارتفاع توتر وريد الباب ، ولكن لا يتيح التنبؤ بدرجة الدوالي.